Effect of Boric Acid on Volatile Products of Thermooxidative Degradation of Epoxy Polymers; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Nazarenko O. B. Olga Bronislavovna; Bukhareva P. B.; Melnikova T. V.; Putkhenpurakalchira M. V. Maniyan Visakkh (2016, 2016)
Title screen